Pelaksanaan Kebijakan Penempatan Alat Tangkap Ikan di Zona Penangkapan Ikan Terukur dan Wilayah Pengelolaan Perikanan Nelayan Tradisional Kelurahan Dabo Lama - Hendra Wiguna (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The existence of the grouping of traditional fishermen in Dabo Lama and also the Regulation of the Minister of Marine Affairs and Fisheries Number 36 of 2023 concerning the Placement of Fishing Gear and Fishing Aids in the Measured Fishing Zone and Traditional Fisherman's Fisheries Management Area, has made the local government enforce this regulation in the area. The purpose of this study is to find out the implementation of the Regulation of the Minister of Marine Affairs and Fisheries Number 36 of 2023 concerning the Placement of Fishing Gear and Fishing Aids in the Measured Fishing Zone and the Traditional Fisheries Management Area, Dabo Lama Village. The research approach used is a qualitative approach. The results of the study show that the ideal policy dimension in the Regulation of the Minister of Marine Affairs and Fisheries Number 36 of 2023 concerning the Placement of Fishing Gear and Fishing Aids in the Measured Fishing Zone shows quite effective results in the context of implementation in Dabo Lama Village. The policy is considered relevant to the needs of traditional fishermen and is able to create a more harmonious pattern of interaction between fellow fishermen, as well as between fishermen and the implementing body. Then the target group dimension shows the result that the policy is highly dependent on the equitable delivery of information, the involvement of the target group in decision-making, and the support of adequate means to support traditional fishers in carrying out the stipulated provisions Then the implementation body dimension shows the result that there are limited resources from the implementing body, such as the number of supervisory officers and facilities inadequate supporters. This condition has an impact on the less optimal assistance provided to fishermen in understanding and implementing policies in accordance with the rules that have been set. Then from the dimension of environmental factors, the results show that there are local initiatives from the government and the community to improve environmental conditions, such as mangrove replanting programs and communitybased waste management.